Societal changes in Ancient Greece impacted terrestrial and marine environments - Koutsodendris, Andreas; Maran, Joseph; Kotthoff, Ulrich; Lippold, Jörg; Knipping, Maria; Friedrich, Oliver; Gerdes, Axel; Kaboth-Bahr, Stefanie; Bahr, André; Schulz, Hartmut; Sakellariou, Dimitris; Pross, Jörg (Communications earth & environment, 2025)
The Aegean hosts some of the earliest cultural centers in European antiquity. To reconstruct the evolution of early anthropogenic impact in this region, we have examined lead (Pb) contents and vegetation dynamics on well-dated environmental archives extending to the early Holocene. We show that the impact of agropastoral societies on terrestrial ecosystems was locally confined during the Bronze and Iron Ages (5200-2750 years ago), although we record an onset of Pb pollution already at 5200 cal. years BP and thus about 1200 years earlier than previous archeological evidence. Our data demonstrate a marked increase in Pb pollution at 2150 cal. years BP that left an imprint across terrestrial and marine settings of the Aegean region. This first manifestation of marine pollution coincides with maximum deforestation and agricultural expansion, signaling pervasive human impact on ecosystems connected to the advanced monetized societies during the Hellenistic and Roman periods in Ancient Greece.